Nature and effectiveness of extension services provided by producers organization - Nikam, Vinayak; Singh, Premlata; ., Satyapriya; Sharma, D.K. (Annals of Agricultural Research, 2016)
Mahagrapes was established in the year 1991 as marketing partner to grapes growers’ cooperative. Many studies indicate that it has helped grape growers from Maharashtra to increase their income and export competitiveness by providing good extension services to the members. Therefore study was conducted to study the nature and effectiveness of services of Mahagrapes with 90 grapes growers who were members of cooperatives linked to Mahagrapes from Nashik, Sangli and Pune districts of Maharashtra. Data were collected through focused group discussion and personal interview of the farmers. Regarding nature of extension services of Mahagrapes it was found that Mahagrapes provided biobased pesticides to the members. Mahagrapes consultants provided consultancy services about Good Agricultural Practices (GAP) standards, cultural practices, weather, harvesting etc. Mahagrapes provided all support during marketing operations like grading, packaging, transport cooling and storage. It also was involved in extension activities like demonstrations, trainings, group meetings and farm tours. Overall effectiveness index score with indicators satisfaction, knowledge and adoption was 92.34 percent indicating high effectiveness of services. Thus, quality and effective services provided by the producers’ organizations have direct bearing on the success of organization and satisfaction of the members